Implementation problems of activity- based costing method (ABC) - Giedrė Laurinavičienė (Business: Theory and Practice, 2011)
Activity- based costing method (ABC) is quite a new and modern product costing method. However, many aspects of this method are not examined enough or interpreted differently in the economic literature. Lithuanian companies do not use this method or use only its separate components. Activity- based costing method is useful because it calculates products’ cost, assesses the effectiveness of activities and manages costs of activities. This article analyzes ABC method’s importance and its place in product costing methods’ system, advantages and reasons which prevent from using this method in Lithuanian companies. This article analyzes the main implementation stages: 1) identification of activities which take place in organization; 2) calculation of the costs of each activity; 3) determination of cost drivers and coefficients of cost drivers for each activity; 4) calculation of products’ cost.